Efektivitas Penggunaan Media Daring SIAKAD Terhadap Pemenuhan Kebutuhan Informasi Akademik di Kalangan Mahasiswa Universitas Islam Makassar - nfn Sutriani; Anil Hukmah; nfn Andriansyah (Journal of Communication Sciences (JCoS), 2020)
The rapid development of technology encourages Makassar Islamic University to make changes in the academic information system, which was originally done manually / traditionally to online-based which can be accessed anywhere and anytime by students to meet the need for academic information. Various problems occur in the implementation of the online-based information system, so the assumptions that arise regarding how the effectiveness of the use of SIAKAD Online Media to meet the academic information needs of Makassar Islamic University students are the challenges of this research.In this study a quantitative method is used which aims to determine the effect of using online SIAKAD in meeting academic information needs among students. Respondents in this study were drawn from 2017 class year students from 8 faculties totaling 1,194 people. The samples chosen in this study were 299 people with 5% specimens. The research data were obtained through a survey of respondents with Kearis distribution. Then processing and data analysis is done with a simple linear regression analysis using the help of SPSS version 25. The results of this study indicate that there is effectiveness of the use of online data to meet the needs of academic information of students assessed significantly adjusted Rsquare results of 0.305% variation of the dependent variable, namely the fulfillment of needs. This means that 30.5% of the variable fulfillment of needs is the contribution of the variable use of online data